How do consumers interpret the macroeconomic effects of oil price fluctuations? Evidence from U.S. survey data - Martin Geiger; Johann Scharler (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2018)
We use survey data to study how consumers assess the macroeconomic effects of structural oil market shocks on the U.S. economy using vector autoregressive models. To structurally decompose oil price changes, we impose sign restrictions on impulse responses. We find that the survey respondents' expectations are qualitatively in line with the actual developments in most cases. Nevertheless, survey respondents underestimate the adverse effects of oil market shocks in some cases. We also find that respondents expect the central bank to stabilize inflation as well as output and that expectations are consistent with a standard Taylor rule.
Keywords: E00; E32; D84; 330; Macroeconomic Expectations; Michigan Survey; Structural Vector Autoregression; Zero and Sign Restrictions